Persepsi Mahasiswi Tentang Kanker Payudara dan Perilakunya terhadap Pencegahan Kanker Payudara di Fakultas Keperawatan Universitas Andalas - Ria Delviani.R.S; Vetty Priscilla (Fakultas Keperawatan Universitas Andalas, 2014)
The incidence of the breast cancer has increased dramatically every year, approximately 68,6 % women with breast cancer go to get treatment at the advanced stage, so they get difficult to be cured, while the breast cancer could be detected at the beginning stage through breast self-examination or BSE. BSE is the most effective way for early prevention of breast cancer. The perceptions about breast cancer will affect one's BSE behavior. The purpose of this study was to know the perception of breast cancer susceptibility and severity, also the perception of the benefits and barriers of student BSE and found out the relation between the perceptions with BSE behavior. This study was analytical used cross-sectional design, it was done from January up to June 2013. The sample of this study included 76 students of nursing and they were taken by using stratified random sampling. Using univariate analysis, and bivariate (with Chi Square Test). The result of the study indicated that about 59,2 % respondents had BSE behavior is not well, 52,6% respondents have perceptions of positive susceptibility, 52,6% respondents have perceptions of negative severity. 59,2% respondents have perceptions of benefits negative and 52,6% respondents have perceptions of barrier negative. There is a relation between the perceptions susceptibility, severity, benefits, barrier with BSE behavior. Necessary to increase the role of educators in providing information about breast cancer and its early detection, to be improving student knowledge and skills in the application.